Caracterização do uso de fluconazol em UTI adulto - Salci, Tânia Pereira (2011)
Hospital-acquired infections (HAI) are a major public health problem. In the recent decades, the participation of fungi in the etiology of these infections has increased considerably, and they are responsible for nearly 20% of infections in intensive care units (ICU). ICU patients are often affected by fungal infections due to multiple factors that lead to impaired defense mechanisms. The mortality rates in critically ill patients suffering from invasive fungal infections range between 40 and 70%. Antibiotics, on the other hand, play an important role in health care. However, the inappropriate use of these drugs causes serious consequences, such as induction of microbial resistance and unwanted therapeutic effects. In clinical practice we have a limited antifungal arsenal. The delay in beginning an appropriate antifungal therapy in critically ill patients has a significant impact on morbidity and mortality. Furthermore, the choice of suitable antifungal, with an adequate dosage and time of treatment are essential for a successful treatment. Studies have shown the inadequate use of antifungal agents in up to 89% of cases, which increases the average length of hospital stay and the costs of hospitalization. Studies of drug utilization contribute to diagnose problems related to their usage. The ATC/DDD method is a tool that makes it possible to quantify and compare the use of drugs in different institutions and even countries, providing information to clarify what are the points that are worth noticing by the health team in order to improve its services.